A Study on Causes of Students Unrest in Higher Educational Institutions with Special Reference to the colleges of Sivasagar District of Assam - Swapna Lahon (International Journal of Advanced Science and Technology, 2020)
The progress and development of a country is mainly based on the dedication and hard work of its students and their innovative ideas and thoughts. They are our assets. They are always ready to sacrifice their lives for the country. But the ongoing rapid frustration among the students of higher educational institutions leads them to darkness. They are deviated from the social norms. They are showing discontentment behavior against existing norms in the institutions. Thus the problem of students’ unrest is becoming a threatening to the whole education system. The study mainly deals with the causes of students’ unrest in higher education. The researcher tried to find out the causes behind students’ unrest. A self-structured close ended questionnaire was administered to collect data from the sample. The findings of the study indicate that there are slightly, moderately and highly affectedcauses of students’ unrest. This study will help the administrators, teachers and parents to redress the problem of students’ unrest.